HISTORICAL AND CIVIC EDUCATION FIELD: CHALLENGES AND CONSEQUENCES OF THE WAR - Олексенко, Світлана; Савченко, Світлана (SWorldJournal, 2024)
Ukrainian education in the conditions of war faces challenges that require changes in approaches to the organization of educational activities, consideration of factors of external influence, the search for effective forms, methods and means of training s